Foreign direct investment, financial Development, international trade and energy consumption: Panel data evidence from selected ASEAN Countries - Zainal Abidin, Irwan Shah; Haseeb, Muhammad; Azam, Muhammad; Islam, Rabiul (International Journal of Energy Economics and Policy, 2015)
The main purpose of this study is to examine the linkage among energy consumption, Foreign Direct Investment (FDI), financial development and trade for the selected ASEAN countries namely Indonesia, Malaysia, the Philippines, Singapore, and Thailand. After employing appropriate tests of stationarity, long run-relationship and Granger causality test reveals that there exists significant long-run relationship among all explanatory variables namely FDI inflows, trade, financial development and energy consumption. The ARDL bound tests approach further confirms the long-run relationship among set of regressors. Results on Granger causality reveal that in the short-run unidirectional causality running from FDI inflows to energy consumption, energy consumption to financial development, and energy consumption to trade. Whereas, results also show that there exists bidirectional causality between trade and energy consumption, energy consumption and FDI, trade and FDI, energy consumption and financial development, trade and financial development during the period under the study. The empirical results reveals that policy makers needs to formulate appropriate and prudent policy to encourage FDI inflows, improve financial sector development, expand exports volume and sustained energy supply, while keep in mind to achieve sustainable economic growth and development in the ASEAN region. Keywords: FDI; financial development; trade; energy consumption; ASEAN JEL Classifications: Q43